Prognostic value of the lactate-to-albumin ratio in critically ill chronic heart failure patients with sepsis: insights from a retrospective cohort study - Junqi Gou; Chaohui Liu; Mingjian Lang; Fengyou Yao (Frontiers in Medicine)
Background and objectivesCritically ill patients with chronic heart failure (CHF) complicated with sepsis are associated with a high mortality risk. The lactate-to-albumin ratio (LAR) has been shown to correlate with poor prognosis in various critical illnesses. However, the relationship between LAR and the short-and long-term prognosis of critically ill patients with CHF and sepsis has not been thoroughly explored. Therefore, this study aimed to evaluate the prognostic value of LAR in critically ill patients with CHF and sepsis.MethodsA retrospective analysis was conducted on the clinical data of 2,416 ICU-managed critically ill patients with CHF and sepsis. Based on the optimal cutoff value, patients were divided into higher LAR and lower LAR groups. Multivariable Cox proportional hazards models were used to assess the association between LAR and all-cause mortality at different time points (ICU, in-hospital, 14-day, 28-day, and 90-day). Kaplan–Meier survival curves were used to evaluate the differences in all-cause mortality risk between the two groups. The receiver operating characteristic (ROC) curve is used to evaluate the predictive ability, sensitivity, specificity, and area under the curve (AUC) of LAR for predicting in-hospital mortality in patients with CHF and sepsis. Restricted cubic spline (RCS) analysis was performed to examine the potential dose–response relationship between LAR and all-cause mortality at each time point. Subgroup analyses further explored the impact of patient characteristics on the prognostic value of LAR.ResultsLAR was significantly associated with ICU, in-hospital, 14-day, 28-day, and 90-day all-cause mortality. The higher LAR group had a higher risk of death compared to the lower LAR group (all p < 0.001). Cox regression analysis confirmed that LAR was an independent prognostic factor for ICU, in-hospital, 14-day, 28-day, and 90-day all-cause mortality in critically ill patients with CHF and sepsis. Kaplan–Meier survival curves further confirmed the significant association between LAR and poor prognosis. The ROC curve analysis shows that LAR has a better predictive value for the prognosis of patients with CHF and sepsis compared to lactate and albumin. RCS analysis demonstrated a linear relationship between LAR and ICU, in-hospital, 14-day, 28-day, and 90-day all-cause mortality. Subgroup analyses revealed consistent prognostic effects of LAR across different clinical subgroups, with no significant interaction observed.ConclusionLAR is an independent predictor of short-term and long-term all-cause mortality in critically ill patients with CHF and sepsis. LAR has the potential to serve as a valuable prognostic biomarker in this population, providing significant implications for clinical decision-making and patient management.